2016
DOI: 10.1002/2016gl068893
|View full text |Cite
|
Sign up to set email alerts
|

Fault slip controlled by stress path and fluid pressurization rate

Abstract: The practice of injecting fluids into the crust is linked to regional increases in seismicity. Increasing fluid pressure along preexisting faults is believed to enhance seismicity rates by reducing the shear stress required for slip, but the processes that cause faults to slip under conditions of fluid pressurization are poorly constrained. We use experimental rock deformation to investigate the controls of fluid pressurization and pressurization rates on fault slip style. We show that pore fluid pressurizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 39 publications
7
54
0
Order By: Relevance
“…From triaxial shear experiments on permeable and impermeable sandstones with saw-cut fractures, Rutter and Hackston (2017) demonstrated that dynamic slip may be easily generated by fluid pressurization in the case of a less permeable rock matrix. Creep experiments conducted on carbonate-bearing and shale-bearing fault gouges by increasing pore pressure under conditions of constant shear stress indicate that dynamic slip instability may be triggered, even if fault friction is characterized by rate-strengthening behavior (Scuderi et al, 2017;Scuderi & Collettini, 2018). French Melodie et al (2016 performed axial compression and lateral relaxation tests on permeable sandstones with saw-cut surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…From triaxial shear experiments on permeable and impermeable sandstones with saw-cut fractures, Rutter and Hackston (2017) demonstrated that dynamic slip may be easily generated by fluid pressurization in the case of a less permeable rock matrix. Creep experiments conducted on carbonate-bearing and shale-bearing fault gouges by increasing pore pressure under conditions of constant shear stress indicate that dynamic slip instability may be triggered, even if fault friction is characterized by rate-strengthening behavior (Scuderi et al, 2017;Scuderi & Collettini, 2018). French Melodie et al (2016 performed axial compression and lateral relaxation tests on permeable sandstones with saw-cut surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A few researchers have conducted triaxial-injection shear tests on saw cut fractures (Bauer et al, 2016;French et al, 2016;Nemoto et al, 2008;Rutter & Hackston, 2017). French et al (2016) conducted saw cut fracture slip tests on dry or saturated sandstones (permeable Berea and Darley Dale sandstones) to investigate the effects of stress path and fluid pressurization rate on fracture slip characteristics (slip velocity, shear stress drop, etc.). Rutter and Hackston (2017) competed similar triaxial shear tests on permeable (Darley Dale sandstone) or impermeable (tight Pennant sandstone) saw cut fractures to study friction change and shear failure of fractured rocks with or without gouge.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have investigated the role that P f has on fault stability with different results (French et al, ; Ikari et al, ; Rutter & Hackston, ). For instance, Sawai et al () demonstrate that decreasing effective pressure ( σn) causes a transition from stable to unstable slip behavior in blueschist samples.…”
Section: Introductionmentioning
confidence: 99%
“…Ougier‐Simonin and Zhu (, ) also observed that shear localization in porous rocks could become unstable by decreasing effective pressure as pore pressure increases during the post failure stage of faulting. In addition, French et al () and Scuderi et al () show that fluid pressurization can overcome velocity‐strengthening friction to result in accelerated fault slip. On the other hand, slow slip events may arise or when the effective pressure is low (e.g., Leeman et al, ), and the low σn associated with high pore fluid pressure is expected to stabilize slip.…”
Section: Introductionmentioning
confidence: 99%